L-arabinose co-ingestion delays glucose absorption derived from sucrose in healthy men and women: a double-blind, randomised crossover trial. Issue 6 (28th September 2022) - Pasmans, Kenneth; Meex, Ruth C.R.; Trommelen, Jorn; Senden, Joan M.G.; Vaughan, Elaine E.; van Loon, Luc J.C.; Blaak, Ellen E.
Abstract: Dietary interventions to delay carbohydrate digestion or absorption can effectively prevent hyperglycaemia in the early postprandial phase. L-arabinose can specifically inhibit sucrase. It remains to be assessed whether co-ingestion of L-arabinose with sucrose delays sucrose digestion, attenuates subsequent glucose absorption and impacts hepatic glucose output. In this double-blind, randomised crossover study, we assessed blood glucose kinetics following ingestion of a 200-ml drink containing 50 g of sucrose with 7·5 g of L-arabinose (L-ARA) or without L-arabinose (CONT) in twelve young, healthy participants (24 ± 1 years; BMI: 22·2 ± 0·5 kg/m 2 ). Plasma glucose kinetics were determined by a dual stable isotope methodology involving ingestion of (U- 13 C6 )-glucose-enriched sucrose, and continuous intravenous infusion of (6, 6– 2 H2 )-glucose. Peak glucose concentrations reached 8·18 ± 0·29 mmol/l for CONT 30 min after ingestion. In contrast, the postprandial rise in plasma glucose was attenuated for L-ARA, because peak glucose concentrations reached 6·62 ± 0·18 mmol/l only 60 min after ingestion. The rate of exogenous glucose appearance for L-ARA was 67 and 57 % lower compared with CONT at t = 15 min and 30 min, respectively, whereas it was 214 % higher at t = 150 min, indicating a more stable absorption of exogenous glucose for L-ARA compared with CONT. Total glucose disappearance during the first hour was lower for L-ARA compared with CONT (11 ± 1 v . 17 ± 1 g, P < 0·0001). Endogenous glucose production was not differentially affected at any time point ( P = 0·27). Co-ingestion of L-arabinose with sucrose delays sucrose digestion, resulting in a slower absorption of sucrose-derived glucose without causing adverse effects in young, healthy adults.